2016
DOI: 10.18632/oncotarget.13757
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphiphilic folic acid-cholesterol-chitosan micelles for paclitaxel delivery

Abstract: In order to decrease the toxicity of paclitaxel (PTX) and increase the efficiency, we developed an amphiphilic PTX injection system using a biodegradable and biocompatible polymer synthesized by folic acid, cholesterol, and chitosan (FACC). This FACC-based polymer had a low critical concentration (64.13μg/ml) and could self-assemble in aqueous condition to form nanoscale micelles. The particle sizes of FACC-PTX micelles were 253.2±0.56 nm, the encapsulation efficiency and loading capacity of these FACC-PTX mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Moreover, the abundant active amine and hydroxyl groups in CS could offer many opportunities for chemical modification. In recent years, several chitosan-based PTX delivery systems have been developed, such as N -mercapto acetyl- N ′-octyl- O , N ′′-glycol chitosan micelles [ 13 ], 3,6- O , O ′-dimyristoyl chitosan micelles [ 14 ], folic acid–cholesterol–chitosan micelles [ 15 ], PTX conjugated trimethyl chitosan nanoparticles [ 16 ], palmitoyl chitosan nanoparticles [ 17 ], N -succinyl-chitosan nanoparticles [ 18 ] and PTX-loaded chitosan nanoparticles prepared by the nano-emulsion method [ 19 ]. However, chitosan with high molecular weight has poor solubility in aqueous medium at neutral pH, which limits its medical and pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the abundant active amine and hydroxyl groups in CS could offer many opportunities for chemical modification. In recent years, several chitosan-based PTX delivery systems have been developed, such as N -mercapto acetyl- N ′-octyl- O , N ′′-glycol chitosan micelles [ 13 ], 3,6- O , O ′-dimyristoyl chitosan micelles [ 14 ], folic acid–cholesterol–chitosan micelles [ 15 ], PTX conjugated trimethyl chitosan nanoparticles [ 16 ], palmitoyl chitosan nanoparticles [ 17 ], N -succinyl-chitosan nanoparticles [ 18 ] and PTX-loaded chitosan nanoparticles prepared by the nano-emulsion method [ 19 ]. However, chitosan with high molecular weight has poor solubility in aqueous medium at neutral pH, which limits its medical and pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation efficiency (EE%) and drug loading (DL%) were determined as described previously [ 26 ]. Briefly, 0.5 mL DEX-SS-IND/PTX micelle solution was dissolved in 9.5 mL DMSO to dissolve all PTX.…”
Section: Methodsmentioning
confidence: 99%
“…Folic acid conjugated nanomedicines has also reported to increase the efficacy of paclitaxel and cisplatin in cervix cancer cells facilitating the intracellular uptake. In vitro studies in Hela cells (FR-α positive) have demonstrated that paclitaxel micelles [12] and gelatin nanoparticles loaded with cisplatin [13] and decorated with folic acid improve the inhibition of cell proliferation, increasing therapeutic efficacy. This inhibition improvement of folate decorated micelles of PTX was not observed in A459 lung adenocarcinoma cells (FR-α negative), showing a similar efficacy than non-targeted formulations and indicating that folic acid conjugation is the responsible of the enhancement of anticancer efficacy [13] (Table1).…”
Section: Cervix Cancermentioning
confidence: 99%